Kekuatan Politik Dewan Adat Suku dalam Pemilihan Kepala Daerah di Kabupaten Jayapura Tahun 2017 - Masni Banggu; Arie Purnomo; Asriani asriani (Universitas Muhammadiyah Sorong, 2021)
This study aims to describe the political power of the Tribal Customary Council in providing support to regional head candidates in the 2017 Simultaneous Regional Head Elections in Jayapura Regency. This type of qualitative research with ethnographic type. Determination of informants is done purposively. Data was collected through interviews and literature review. The developed data describes, describes, and analyzes in detail the culture and customs based on the research objectives. The results showed that the nine Tribal Customary Councils in Jayapura Regency supported the candidate for Regent Mathius Awaitouw for the 2017-2022 period. The Tribal Customary Council (DAS) has a strong influence on the lives of local people, so that in the election of regional heads, the watershed is often the place where candidates for regional heads ask for permission and blessing.